Psychology well- being at workplaces - Ismail, Fadillah; Abd Razak, Nur Azwany; Abdul Kadir, Adibah; Chan, Shiau Wei; Ismail, Siti Norziah (Penerbit UTHM, 2020)
Psychological well-being indicates the existence of positive relationships with others, personal personality, autonomy, meaning in life, and personal growth and development. According to Ronald (2017), psychology well-being is a balance between challenging life events and rewarding, and is achieved through a balance of affected life events.